Antecedents and Impacts of Psychological Ownership Among Academicians in Business Faculties of Malaysian Public Universities - Muniandy, Nanthini (2007)
Research on the impact of psychological ownership and its antecedents is at an inchoate stage. Earlier studies have considered only work factors as antecedents of psychological ownership. This study introduces non-work factors as potential antecedents. Work factors comprise of autonomy, participative decision-making and job tenure, while non-work factors consists of self-efficacy and locus of control. This study also investigates the impact of psychological ownership on job performance mediated through job commitment and job satisfaction. Unlike previous studies, this study has been carried out in an eastern setting. The study was carried out amongst lecturers in business schools of public universities in Malaysia. Questionnaires were distributed through paper and online survey. Three hundred and twenty nine (329) academicians participated in this study. The data analyses reveal that, with regards to work factors, only autonomy and participative decision-making are positively related to psychological ownership. In terms of nonwork factors, self-efficacy and locus of control have a stronger influence on psychological ownership, compared to work factors. This study measured job performance as a multidimensional construct with three dimensions (teaching, publication and ESP [Editorial, Supervisory and Professional]) using actual and perceived performance ratings. Findings indicate that psychological ownership is positively related to job performance, job commitment and job satisfaction. Theoretically, this study depicts the importance of dispositional traits as predictors of psychological ownership, and psychological ownership as a determinant of employee performance. Practically, this study provides a mechanism to improve job performance of academicians in Malaysian public universities. The present study indicates ways to develop psychological ownership among lecturers as well as recommends administrators to incorporate personality tests in recruiting academic staffs in universities. On the whole, this study contributes to the present knowledge of psychological ownership by integrating several antecedents and outcomes in a single, comprehensive model of psychological ownership.